Possible future scenarios in the gateways to the Arctic for Subarctic and Arctic marine systems: II. prey resources, food webs, fish, and fisheries. (8th October 2021) - Mueter, Franz J; Planque, Benjamin; Hunt, George L; Alabia, Irene D; Hirawake, Toru; Eisner, Lisa; Dalpadado, Padmini; Chierici, Melissa; Drinkwater, Kenneth F; Harada, Naomi; Arneberg, Per; Saitoh, Sei-Ichi
Abstract: Climate change impacts are pronounced at high latitudes, where warming, reduced sea-ice-cover, and ocean acidification affect marine ecosystems. We review climate change impacts on two major gateways into the Arctic: the Bering and Chukchi seas in the Pacific and the Barents Sea and Fram Strait in the Atlantic. We present scenarios of how changes in the physical environment and prey resources may affect commercial fish populations and fisheries in these high-latitude systems to help managers and stakeholders think about possible futures. Predicted impacts include shifts in the spatial distribution of boreal species, a shift from larger, lipid-rich zooplankton to smaller, less nutritious prey, with detrimental effects on fishes that depend on high-lipid prey for overwinter survival, shifts from benthic- to pelagic-dominated food webs with implications for upper trophic levels, and reduced survival of commercially important shellfish in waters that are increasingly acidic. Predicted changes are expected to result in disruptions to existing fisheries, the emergence of new fisheries, new challenges for managing transboundary stocks, and possible conflicts among resource users. Some impacts may be irreversible, more severe, or occur more frequently under anthropogenic climate change than impacts associated with natural variability, posing additional management challenges.